2016
DOI: 10.1038/ncomms12567
|View full text |Cite
|
Sign up to set email alerts
|

Cep295 is a conserved scaffold protein required for generation of a bona fide mother centriole

Abstract: Centrioles surrounded by pericentriolar material (PCM) serve as the core structure of the centrosome. A newly formed daughter centriole grows into a functional mother centriole. However, the underlying mechanisms remain poorly understood. Here we show that Cep295, an evolutionarily conserved protein, is required for generation of a bona fide mother centriole organizing a functional centrosome. We find that Cep295 is recruited to the proximal centriole wall in the early stages of procentriole assembly. Cep295 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 49 publications
(78 reference statements)
3
72
0
Order By: Relevance
“…Importantly, recruitment of Asl in Drosophila embryos only occurs after disengagement, indicating that these licensing processes occur sequentially 93 . In mammalian cells, CEP295 directly binds to CEP192 and contributes to the stabilization of centrioles after the loss of the cartwheel upon mitotic exit 89,94 . Considering that CEP152 and CEP192 form scaffolds for the recruitment of PLK4 9599 , the kinase essential for centriole duplication (see below), these results explain why post-mitotic PCM assembly is required to confer duplication competence to procentrioles 91 .…”
Section: Control Of Centriole Numbermentioning
confidence: 99%
“…Importantly, recruitment of Asl in Drosophila embryos only occurs after disengagement, indicating that these licensing processes occur sequentially 93 . In mammalian cells, CEP295 directly binds to CEP192 and contributes to the stabilization of centrioles after the loss of the cartwheel upon mitotic exit 89,94 . Considering that CEP152 and CEP192 form scaffolds for the recruitment of PLK4 9599 , the kinase essential for centriole duplication (see below), these results explain why post-mitotic PCM assembly is required to confer duplication competence to procentrioles 91 .…”
Section: Control Of Centriole Numbermentioning
confidence: 99%
“…Therefore, to distinguish whether these excess Cep192 dots reflect centrosome amplification, centriole disengagement, or PCM fragmentation, we next performed immunofluorescence analyses using specific antibodies against centriolar glutamylated microtubules (GT335) and Cep152, a mother centriole marker, in lymphocyte cells (Tsuchiya et al. ). We found that, in the CHAMP1 ‐mutant patient's cells, all Cep192 foci on the multipolar spindle poles contained GT335 dots (Fig.…”
mentioning
confidence: 99%
“…Recently, Cep295 is identified as the key protein for the conversion of daughter centrioles into functional mother centrioles, and the loading of Cep152 by Cep135 and Cep295 to daughter centrioles is critical for the conversion (Fu et al, 2016; Tsuchiya et al, 2016). Interestingly, Cep295 is only required for targeting of Cep152 to the young mother centriole, but not to the old mother centriole, implying that other scaffold proteins might play a role in anchoring Cep152 to the old mother centriole.…”
Section: Resultsmentioning
confidence: 99%